Сутність людського капіталу підприємства - Іваненко, Л.В. (Стратегія і механізми регулювання промислового розвитку, 2014)
На основі систематизації існуючих трактувань конкретизоване поняття «людський капітал підприємства». Виявлено диспропорції в динаміці продуктивності праці та реальної заробітної плати. Встановлено, що структура сукупних споживчих витрат населення не сприяє розширеному відтвореннюлюдського капіталу в Україні. Обґрунтовано необхідність підвищення рівня інвестиційної активності підприємств щодо компенсації недостатніх можливостей розширеного відтворення людського капіталу працівників. На основе систематизации существующих трактовок конкретизировано понятие «человеческий капитал предприятия». Выявлены диспропорции в динамике производительности труда и реальной заработной платы в промышленности в Украине. Указывается, что структура совокупных потребительских расходов населения не способствует расширенному воспроизводству человеческого капитала в Украине. Обоснована необходимость повышения уровня инвестиционной активности предприятий для компенсации недостаточных возможностей расширенного воспроизводства человеческого капитала. The concept of «company's human capital» was further elaborated on the basis of systematization of existing interpretations. The human capital of the company was asked to consider the totality of the qualitative characteristics of employees: abilities, skills, knowledge, motivation, educational and cultural development, health which are formed in the process of their livelihoods by investing and are used in economic activity, as well as created in the enterprise environment efficient use and development of these characteristics. Disproportions were found in the dynamics of labor productivity and real wages in the industry in Ukraine. Dynamics points to inefficiency and inadequate investment in human capital as increasing wages in the industry does not provide the appropriate growth returns to a more efficient applying of human capital. The article indicates that structure of total consumer spending is not conducive to the expanded reproduction of human capital in Ukraine.The low level of activity of the companies in the field of human capital investment is caused by that staff costs are not considered by them as an effective investment for profit in the future, but only as an expense of the period in which they are made. The investment human capital of the company are expedient provided a sufficiently high level of payback and profitability. Employers, for the most part, evaluate the educational level of young professionals as necessary, but not sufficient factor and its own work to address gaps in the knowledge of young professionals - graduates of local universities. Commercial companies is an issue about the effectiveness of staff development programs as ineffective programs may not be the investment in human capital, but inefficient operating costs. The article substantiates the necessity to improve the investment activity to compensate for the lack of capacity of expanded reproduction of human capital.